Rural Electrification Program in Indonesia: Comparing SEHEN and SHS Program - Sambodo, Maxensius Tri (UI Scholars Hub, 2015)
In 2014, the Indonesian government has targets to obtain 80% of electrification ratio and 98.9% of ruralÂ electrification ratio. Extending the grid and off-grid connection has been done to obtain the targets. ThisÂ paper aims to compare two main programs on rural electrification namely Super Extra Energy Saving (SuperÂ Ekstra Hemat Energi, SEHEN) that is belong to PLN (state owned company in electricity) and the Solar Home System (SHS) that is financed by the Ministry of Energy and Mineral Resources (MEMR). IndonesiaÂ has started the rural electrification program in the late 1950s, but how to provide electricity in a sustainableÂ ways both organizationally and institutionally still become a big challenge. The experiences from East Nusa Tenggara provinces showed that both SEHEN and SHS can instantly improve electrification ratio, but governmentÂ needs to synchronize the technical, administrative, and financial aspect from the two programs. Without any improvements in designing the program, we argue that the existing program is not sustainable.